Nutritional Analysis of Sweet Orange Peel Extract for Development of Obesity Treatment - Winda Rizki Pebrina Batubara; Tri Nugraha Susilawati; Dono Indarto (Global Health Science Group, 2023)
Obesity is a complex chronic disease that becomes the main factor of cardiometabolic diseases such as heart diseases, stroke and diabetes mellitus. Oxidative stress is involved in the obesity pathogenesis. Diet and physical exercise are recommended for obesity treatment but many obese people have low compliance to these treatments. Sweet orange (Citrus sinensis L.) is an Indonesian fruit with high production per year. This fruit pulp contains high vitamin C level, which is widely used as a strong anti oxidant to inhibit oxidative stress. However, sweet orange peel is just thrown in the soil and becomes rubbish. Therefore, the aim of this study was to analyze nutritional contents of sweet orange peel extract (OPE). Fresh orange peels were obtained from a local market at the Surakarta city and the dried orange peels were extracted using ethanol solvent. Carbohydrate, protein, and fat levels were determined using the existing method at the Food Technology Laboratory while vitamin C and Magnesium (Mg) levels were determined using the spectrophotometric and SSA-flame methods respectively. 100g OPE contained 68.88% carbohydrate, 3.23% protein, 3.41% fat, 1556.6 mg vitamin C and 239.74 mg Mg. In conclusion, the OPE is a good source of vitamin C and Mg, which can be developed as a nutraceutical for obesity treatment. Further investigation is required to determine active compounds in the OPE, which enhances the beneficial effects of vitamin C and Mg.